Pelaksanaan Pemungutan Pajak Reklame Oleh Badan Pendapatan Pengelolaan Keuangan dan Aset Daerah Kota Surakarta Berdasarkan Peraturan Walikota Nomor 58 Tahun 2019 - Annisa Fadhila; Rosita Candrakirana (Jurnal Discretie, 2022)
This research aims to find out the implementation of advertisement tax collection in Surakarta City based on the Mayor Regulation Number 58 of 2019 and to find out the obstacles that occur as well as the solutions to the existing obstacles.This research is a presciptive normative legal research using a statutory research approach. The data sources of this research are from primary data sources and secondary data sources. Data collection techniques used is interview at Office of the Regional Financial and Asset Management Revenue Agency (BPPKAD) Surakarta City and also document study or library study used. The analysis technique used in this research is the syllogism method. The results of this research indicate that the implementation of advertisement tax collection in Surakarta City is in accordance with The Mayor Regulation Number 58 of 2019. However, there are still obstacles happen in the implementation of advertisement tax collection in Surakarta City, namely the lack of public awareness in paying taxes on time also there are still many people who put up illegal advertisements or unpermitted advertisements that neglecting the beauty and the environment in Surakarta City.